Hubungan Kekuatan Otot Lengan Dengan Kemampuan Chest Pass Pada Mahasiswa Putra Pendidikan Olahraga STKIP Kie Raha Ternate - Sukardi Muslatubun; Rifaid Saiman; Alief Lam Akhmady (Peneliti.net, 2022)
This study aims to determine the relationship between arm muscle strength and chest pass in male students of sports education STKIP Kie Raha Ternate City. The method used is a survey with correlational analysis techniques. The population in this study were students of STKIP Kie Raha, Ternate City. There is also a sample of 27 students. Data analysis using the product moment pearson at significant level = 0,05 %. The results of the calculation of data analysis of the two variables show that, r-count = 0.977 > at a significant rate of = 0.05%, so it can be concluded that there is a significant relationship between arm muscle strength and chest pass in STKIP Kie Raha students, Ternate City.